Quality Analysis of Railroad Train Shunting Operation Plan Using the Intelligent Body Model - Tao Yu (Advances in Multimedia)
Shunting work is an important component part of railway transport production and is an important link in realizing the train marshalling plan and the train operation map, accelerating the rotation of vehicles, and completing the task of transport production. With the present, the gradual construction of passenger dedicated lines and high-speed train operation bring a new dawn to railroad transportation on the one hand, but on the other hand, high-speed train operation makes the process of train operation more complicated, and the safety hazards and uncontrollable factors of trains are higher than before. Compared with existing lines, passenger dedicated lines put forward higher requirements on the performance of train operation and dispatching system, requiring better real-time, intelligence, and interactive response characteristics of the train operation and dispatching system. The construction of passenger dedicated lines and the increase in train operation speed have put forward higher requirements for safe, on-time, and high-efficiency train operation. The train operation scheduling system is one of the cores of intelligent railroad transportation system, which is the guarantee of safe and on-time train operation. This requires the search for new control strategies to meet the requirements of high-speed train operation and multiple objectives of safety, punctuality, and comfort. Train operation scheduling is a typical distributed system. At present, there are still problems in the safety of railway shunting operations, such as disconnection in management and implementation, failure to revise some rules and regulations, frequent occurrence of obstacles in equipment and facilities, and substandard quality of operators. Therefore, it is necessary to make a systematic analysis of the current situation of railway shunting safety and propose countermeasures and measures. By studying the structure of intelligent body and multi-intelligent body theory, it decomposes the influencing factors of railroad shunting operation, designs the intelligent body model of each element, and applies it in train shunting operation to improve the quality of railroad shunting operation.